Microvascular exudative hyperresponsiveness in human coronavirus-induced common cold. Issue 2 (February 1994) - Greiff, L; Andersson, M; Akerlund, A; Wollmer, P; Svensson, C; Alkner, U; Persson, C G
Abstract : BACKGROUND--The inflammatory response of the airway microcirculation in rhinitis and asthma may be recorded as luminal entry of plasma macromolecules (mucosal exudation). This study examines the exudative responsiveness of the subepithelial microvessels in subjects with and without common cold after inoculation with coronavirus. METHODS--The airway mucosa was exposed to exudative concentrations of histamine (40 and 400 micrograms/ml) before and six days after inoculation. To assess whether mucosal penetration of a topically applied agent was altered, nasal absorption of chromium-51 labelled ethylene diamine tetraacetic acid (51Cr-EDTA, MW 372) was also examined. A nasal pool technique kept the challenge and tracer solutes in contact with the same ipsilateral mucosal surface. Concentrations of albumin in lavage fluids were measured as an index of mucosal exudation of plasma. Nasal absorption of 51Cr-EDTA was determined by the cumulated 24 hour urinary excretion of radioactivity. RESULTS--Nine subjects developed common cold after coronavirus inoculation and 10 remained healthy. Histamine produced concentration dependent mucosal exudation of plasma in all subjects before and after coronavirus inoculation. In subjects with common cold, however, the histamine-induced mucosal exudation was significantly augmented compared with the group without common cold. This exudative hyperresponsiveness is not explained by an increased baseline exudation because the lavage regimen used produced comparably low baseline exudation in both groups of subjects, nor is it explained by an increased penetration of topical histamine because the ability of the nasal mucosa to absorb 51Cr-EDTA was not significantly increased in the subjects with common cold. CONCLUSIONS--An increased proclivity of the airway subepithelial microcirculation to respond with plasma exudation develops during coronavirus-induced common cold. This specific exudative hyperresponsiveness may be a feature of inflammatory airway diseases.